Analisis Kebutuhan Awal Pengembangan Media Pembelajaran Bangun Ruang Prisma Berbasis Augmented Reality di Sekolah Dasar - Iswahyuni; Neni Mariana; Hendratno; Nurul Istiq'faroh (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
Augmented reality-based learning media was developed in helping to improve spatial ability and understanding of mathematical concepts in elementary schools. Before developing learning media, teachers have to analyze initial needs. The purpose of this research is to analyze the initial needs for developing augmented reality-based learning media in elementary schools, especially in prism. The initial needs analyzed include the conditions and description of mathematics learning that have been learned. The research method used is descriptive qualitative research, by using data collection techniques in the form of interviews with fifth grade teachers, direct observation in the class and questionnaires distributed to fifth grade students. The results of the research show that mathematics is still a difficult lesson for students. So far, teachers still use less representative learning media so that students have difficulty understanding the mathematical concept of geometric shapes. Students hope to be able to learn mathematics using technology-based media which can make them more interested in learning and understanding mathematical concepts. The conclusion from the initial needs analysis is augmented reality-based learning media is needed to improve fifth grade students' spatial ability and understanding of mathematical concepts in prism.